A new motion structure for a six-legged insect robot with Bluetooth remote-control - Mazin Abdulelah Alawan; Ali Kadhim Abdulabbas; Oday Jasim Mohammed Al-Furaiji (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This paper focuses on motion which is considered an important issue for insect robots, which consumes significant energy sources in general. We inspired the robot design structure from the challenges that crawling insects face in nature, especially a cockroach. The proposed robot configuration enhanced error scale such as energy modulation, computation, and mass. This paper presents the design and construction of six-legged robot with minimum number of trigger motors and the movement mechanisms used for the leg movements. The insect robot resembles a cockroach in shape and size (1.6 cm × 4 cm) and can move at rates of up to 3.5 cm per second. The robot can operate for up to 260 minutes. Additionally, it has a camera that can rotate more than 60 degrees in response to commands from a smartphone. The 160×120 pixels monochrome "first person" camera transmits video to a Bluetooth radio at a distance of up to 120 meters away at a frame rate of 1 to 5 per second.